Structural Investigation of Chloride Ion-Containing Acrylate-Based Imidazolium Poly(Ionic Liquid) Homopolymers and Crosslinked Networks: Effect of Alkyl Spacer and N-Alkyl Substituents - Mahmoud Al-Hussein; Lisa Ehrlich; Doris Pospiech; Petra Uhlmann (Nanomaterials)
Understanding the interplay between the molecular structure of the ionic liquid (IL) subunit, the resulting nanostructure and ion transport in polymerized ionic liquids (PILs) is necessary for the realization of high-performance solid-state electrolytes required in various advanced applications. Herein, we present a detailed structural characterization of a recently synthesized series of acrylate-based PIL homopolymers and networks with imidazolium cations and chloride anions with varying alkyl spacer and terminal group lengths designed for organic solid-state batteries based on X-ray scattering. The impact of the concentrations of both the crosslinker and added tetrabutylammonium chloride (TBACl) conducting salt on the structural characteristics is also investigated. The results reveal that the length of both the spacer and terminal group influence the chain packing and, in turn, the nanophase segregation of the polar domains. Long spacers and terminal groups seem to induce denser polar aggregates sandwiched between more compact alkyl spacer and terminal group domains. However, the large inter-backbone spacing achieved seems to limit the ionic conductivity of these PILs. More importantly, our findings show that the previously reported general relationships between the ionic conductivity and the structural parameters of the nanostructure of PILs are not always attainable for different molecular structures of the IL side group.